High value manufacturing : advanced research in virtual and rapid prototyping : proceedings of the 6th International Conference on Advanced Research and Rapid Prototyping, Leiria, Portugal, 1-5 October, 2013 /: advanced research in virtual and rapid prototyping : proceedings of the 6th International Conference on Advanced Research and Rapid Prototyping, Leiria, Portugal, 1-5 October, 2013. ([2014]) - Unknown
No abstract available